Pathophysiological disorders in iron metabolism in the development of obesity and metabolic syndrome - Smirnova, Olga V.; Moskalenko, Olga L.; Kasparov, Edward V.; Kasparova, Irina E. (Meditsinskiy sovet, 2022)
Obesity and metabolic syndrome are one of the major public health problems in the 21st century due to their prevalence. Nonalcoholic fatty liver disease, dyslipidemia, type 2 diabetes mellitus, arterial hypertension, chronic inflammation and anemia are non-communicable diseases accompanying obesity. With obesity, there is a violation of iron metabolism, iron deficiency, which further contributes to the development of metabolic disorders. Iron is the second most abundant metal on Earth, and its bioavailability is reduced due to the formation of insoluble oxides, while iron deficiency is the most common nutritional disorder. Iron metabolism in the body is associated with the formation of reactive oxygen species involved in lipid peroxi dation processes. Iron metabolism in the human body is regulated at all levels; dysregulation of any stage of metabolism can lead to iron deficiency and the development of anemia associated with obesity. This review article summarizes data on molecular and cellular abnormalities in iron metabolism in obesity and metabolic syndrome. The aim of our study was to study, according to the literature, pathophysiological disorders in iron metabolism in the development of obesity and metabolic syndrome. In the future, more research is required to study iron metabolism in obesity with the aim of their preventive and therapeutic effects. The role of oxidative stress in impaired iron metabolism in obesity has not been fully studied, while iron deficiency enhances lipid peroxidation processes in antioxidant deficiency. Under these conditions, oxidative stress can damage cells and destroy red blood cells. The question arises whether the restoration of iron homeostasis in obesity can improve metabolic, inflammatory disorders and reduce the manifestation of oxidative stress, becoming a new innovative approach to the treatment of concomitant metabolic diseases associated with obesity.
CRIS-Team Scopus Importer:2023-04-20
Keywords: iron; iron deficiency anemia; metabolic syndrome; obesity; oxidative stress